ANALYSIS OF GENDER REPRESENTATION AND FEMINIST DISCOURSE IN BARBIE AND WONDER WOMAN THROUGH STUART HALL’S REPRESENTATION THEORY - Pratama, Yoga; Pitaloka, Roro Meifi (Universitas Islam Negeri Sunan Gunung Djati, 2025)
This research aims to explore how gender is constructed and represented through feminism in the films Barbie and Wonder Woman, using Stuart Hall’s representation theory, particularly his constructionist approach. Hall’s theory emphasizes that ‘meaning’ is not just a passive reflection; it’s actively shaped by culture, language, symbols, and the interpretation of social contexts. By employing a qualitative research methodology, this study embraces a constructivist paradigm, which aligns with Hall’s (1997) view that media representations are crafted rather than simply mirroring reality. This perspective highlights how cultural and social contexts play a crucial role in shaping the meanings of media texts. The research focuses on how filmmakers encode meaning in their works and how audiences decode it. The findings reveal that this approach enables a critical engagement with the films' content, allowing for the identification of how they interact with societal ideologies. Both films promote feminist themes by showcasing strong female characters who defy social norms and expectations placed on women, highlighting the importance of critically examining gendered expectations, and illustrating how media can positively influence societal views on gender equality.